Structural Design of a Specialized Multi-Sensor Head for Unmanned Aerial Vehicles - Paweł SZCZEPANIAK (pawel.szczepaniak@itwl.pl); Dariusz RODZIK (dariusz.rodzik@wat.edu.pl); Paweł KALINOWSKI (pawel.kalinowski@itwl.pl); Jarosław CISZKOWSKI (jaroslaw.ciszkowski@itwl.pl) (Problemy Mechatroniki)
The article describes a proprietary method for designing a specialized multi-sensor optoelectronic head for unmanned aerial vehicles, capable of surveying war zones as well as detecting and locating injured soldiers. The first section of the article defines the assumptions made in relation to the structural characteristics of the designed head and compares the parameters and capabilities of heads available on the market. The subsequent section of the article describes structural solutions used in the head and discusses selected aspects related to its construction.